Breast cancer-derived DAMPs enhance cell invasion and metastasis, while nucleic acid scavengers mitigate these effects - Elias O.U. Eteshola; Karenia Landa; Rachel E. Rempel; Ibtehaj A. Naqvi; E. Shelley Hwang; Smita K. Nair; Bruce A. Sullenger (Elsevier, 2021)
Breast cancer (BC) is the most common malignancy in women. Particular subtypes with aggressive behavior are major contributors to poor outcomes. Triple-negative breast cancer (TNBC) is difficult to treat, pro-inflammatory, and highly metastatic. We demonstrate that TNBC cells express TLR9 and are responsive to TLR9 ligands, and treatment of TNBC cells with chemotherapy increases the release of nucleic-acid-containing damage-associated molecular patterns (NA DAMPs) in cell culture. Such culture-derived and breast cancer patient-derived NA DAMPs increase TLR9 activation and TNBC cell invasion in vitro. Notably, treatment with the polyamidoamine dendrimer generation 3.0 (PAMAM-G3) behaved as a nucleic acid scavenger (NAS) and significantly mitigates such effects. In mice that develop spontaneous BC induced by polyoma middle T oncoprotein (MMTV-PyMT), treatment with PAMAM-G3 significantly reduces lung metastasis. Thus, NAS treatment mitigates cancer-induced inflammation and metastasis and represents a novel therapeutic approach for combating breast cancer.